Analisis Valuasi Ekonomi Hutan Mangrove Sebagai Dasar Pengembangan Kawasan Ekowisata - Manullang, Helentina Mariance; Lubis, Zulkarnain; Sabrina, Raja (Universitas Galuh, 2025)
This research was conducted for 2 months from June to July 2023 in Pulau Banyak village, Langkat Regency, North Sumatra Province. This research aims to analyze the economic valuation of mangrove ecosystems, which can later be used as the basis for the development of ecotourism areas. This research was conducted using a survey method and data collection was carried out by interviewing the community of Pulau Banyak village both directly and indirectly interacting with the mangrove ecosystem. The number of respondents in this study was 91. The results showed that 72% of respondents worked as fishermen. The results of the economic valuation analysis show that the direct benefit value of mangrove forests in Pulau Banyak village is Rp. 372,240,000.00 per year, the indirect benefit value is Rp. 242,939,008.00 per year. Optional benefits of Rp. 23,787,891.75 per year and the benefits of this mangrove forest of Rp. 3,986,797.5 per year. The total economic value of the mangrove ecosystem of Pulau Banyak village, Langkat Regency is Rp. 642,953,697.25 per year. With this condition, the mangrove forest of Pulau Banyak village, Langkat Regency can be developed as an ecotourism area.